2013
DOI: 10.4081/ripppo.2013.86
|View full text |Cite
|
Sign up to set email alerts
|

The Referential Process as a Common Factor Across Treatment Modalities

Abstract: Abstract. The paper emphasizes the need for a process component in psychotherapy research, and the need for a theoretical framework within which process measures may be designed and validated. The referential process, defined in the context of multiple code theory, provides a general psychological framework for understanding the mechanisms of therapeutic change in different treatment modalities. The referential process includes three major phases: arousal/activation; narrative/symbolizing and reorganizing/refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
(22 reference statements)
1
11
0
1
Order By: Relevance
“…Studying language also has the advantage of making possible the development of measures that tap the elaborative or dissociative processes used by people with respect to the emotions they are experiencing. This study takes as a point of reference the theories and research of Bucci (1997Bucci ( , 2013 and Pennebaker (1982Pennebaker ( , 2011, which connect the linguistic qualities of speech to specific psychological and interpersonal processes. Bucci (1997Bucci ( , 2013 (Maskit and Murphy, 2011;Maskit, 2012;Mariani et al, 2013Mariani et al, , 2020Negri et al, 2019) have developed computerized linguistic measures of what they call the "referential process, " which is based on Multiple Code Theory (MCT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying language also has the advantage of making possible the development of measures that tap the elaborative or dissociative processes used by people with respect to the emotions they are experiencing. This study takes as a point of reference the theories and research of Bucci (1997Bucci ( , 2013 and Pennebaker (1982Pennebaker ( , 2011, which connect the linguistic qualities of speech to specific psychological and interpersonal processes. Bucci (1997Bucci ( , 2013 (Maskit and Murphy, 2011;Maskit, 2012;Mariani et al, 2013Mariani et al, , 2020Negri et al, 2019) have developed computerized linguistic measures of what they call the "referential process, " which is based on Multiple Code Theory (MCT).…”
Section: Introductionmentioning
confidence: 99%
“…This study takes as a point of reference the theories and research of Bucci (1997Bucci ( , 2013 and Pennebaker (1982Pennebaker ( , 2011, which connect the linguistic qualities of speech to specific psychological and interpersonal processes. Bucci (1997Bucci ( , 2013 (Maskit and Murphy, 2011;Maskit, 2012;Mariani et al, 2013Mariani et al, , 2020Negri et al, 2019) have developed computerized linguistic measures of what they call the "referential process, " which is based on Multiple Code Theory (MCT). The referential process is the ability of human beings to translate the continuous and indistinct flow of emotional and sensorial experience into images and words, thus making it mentally manageable and communicable to others.…”
Section: Introductionmentioning
confidence: 99%
“…Bucci and colleagues have done dictionary-based work that measures “Referential activity.” The Therapeutic Cycles Model (TCM) and Heidelberg Structural Change Scale (HSCS) ( OPD Task Force, 2008 ) were also used to investigate therapist-patient dynamic processes across sessions of psychotherapy ( McCarthy et al, 2011 ). In the same perspective, More specifically, the Weighted Referential Activity Dictionary (WRAD) is a dictionary (word list) containing 696 items, with weights ranging between −1 and +1, used for computer modeling of a psycholinguistic variable, referential activity (RA), in spoken and written languages ( Bucci, 2000 , 2013 , 2018 ; Bucci and Maskit, 2004 ).…”
Section: The Contribution Of Psychoanalysis To the Understanding Of Dmentioning
confidence: 99%
“…With this phenomenon certain specific issues emerge in the transference and countertransference experience. Latest research has outlined the importance of the therapists' emotional response for the outcome of therapy (Bucci 2013;Colli et al 2013;Kächele et al 2013). Gelso et al (2002) demonstrated that countertransference management positively correlates with therapy outcomes; the more therapist-trainees were able to deal with their countertransference, the more improvement their clients exhibited at the end of the treatment.…”
Section: Countertransference In Depressionmentioning
confidence: 99%